Why It Matters that Black Men and Queer Women Invented Digital Remix Culture - Kosnik, Abigail De (JCMS: Journal of Cinema & Media Studies, 2019)
The article offers information related to the incention of digital remix culture by black men and queer women. It mentions about technique of extracting segments from existing recordings and using them to form the musical tracks of hiphop songs; and nonqueer and nonfemale people have participated heavily in fan production, digital sampling and gave rise to culture that has proliferated and thrived on the internet primarily through the creative labor of minority musical and fiction artists.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé